E-government through different digital platforms in a group of citizens from an Argentinean city - Alderete, María Verónica; Díaz, Lucía Andrea; Álvarez, Nicolás (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This work analyzes the socio-demographic determinants of the adoption of electronic government by citizens through different digital platforms. A descriptive exploratory analysis is carried out with data from an online survey conducted between October and November 2020 to a group of citizens from Bahía Blanca, Argentina. Three models were estimated according to the definition of electronic government (EG): broad EG (web and social networks), traditional EG (web) and EG by social networks. Among the results, it stands out that citizens use the web more than social networks to contact the local government. The older the citizen, or the higher their educational level, the greater the propensity to EG, except in the last model. Likewise, the female gender positively explains the propensity to perform EG in all the models. In the traditional model, both EG experience and social influence and occupation have a positive effect.